Miss America 2.0 : staying relevant in the #MeToo era - Robson, Karen, (SAGE Knowledge. Cases., 2019)
The Miss America Organization is a non-profit organization best known for its annual pageant in which young women compete for the title of "Miss America." In the pageant, contestants have historically entered into a series of events, including a controversial swimsuit competition. Viewership of the pageant has been declining since 2013, and in 2017 the organization faced a scandal when misogynistic emails from the chief executive were leaked; this scandal coincided with the #MeToo movement, which is intended to expose and combat sexual harassment and assault in the workplace. In the face of the email scandal, declining viewership, and the #MeToo movement, the organization made significant changes to its leadership and to their annual pageant, rebranding the pageant as a competition and eliminating the swimsuit competition component. In this case, students are asked to analyze how the Miss America Organization can balance its history as a pageant with its stated goal of supporting female empowerment.